The Relevance of the Study of Hadith Science in the Context of Contemporary Islamic Economics - Abdul Latif Harahap; Muhammad Habibi Siregar; Juli Julaiha Pulungan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research examines the relevance of hadith science in building foundations and solving contemporary Islamic economic problems. As the second source of Islamic law after the Koran, hadith plays an important role in establishing economic principles and practices in accordance with Islamic teachings. In the modern context, the application of sharia principles such as justice, balance, prohibition of usury, and honest trading originates from the hadith of the Prophet Muhammad SAW. The research method used is the library study method. This research collects and analyzes data from various relevant literature, including books and scientific journals. The research results show that hadith science makes a significant contribution to the development of Islamic economic concepts that are based on sharia values ​​and are able to answer the challenges of the contemporary era. This study confirms that an in-depth understanding of hadith not only enriches Islamic economic literacy, but also becomes the main instrument in formulating fair and sustainable economic policies and practices. Thus, it is hoped that this research will become a reference in developing theories and applications of Islamic economics that are contextual and relevant to the needs of modern society.